Exploring possible influences of HIV/AIDS-related stigma on risky sexual behaviour and childbearing decisions: Cape Town 2002-2009 - Machemedze, Takwanisa (Department of Sociology, 2017)
This dissertation uses survey data to explore HIV/AIDS-related stigma as it is manifested in the general population of young adults in Cape Town and amongst people living with HIV/AIDS (PLWHA) on highly active antiretroviral treatment (HAART) in Khayelitsha (an African township in Cape Town). For the general population, we assessed how 'symbolic stigma' (negative attitudes and moral assessments of PLWHA) was related to risky sexual behaviour and whether this was mediated by perceived risk of HIV infection. For PLWHA, we assessed whether 'internalized stigma' and perceptions of stigmatizing attitudes in the broader population (mediated through disclosure of HIV sero-status to sexual partners and experiences of depression and anxiety symptoms) were associated with condom use. We also assessed the relationship between experiences of stigma, internalization of stigma, perceptions of stigma and childbearing desires of PLWHA The study found out that young Black and Coloured women who held symbolic HIV/AIDS-related stigma attitudes were more likely to perceive themselves at a reduced risk of infection with HIV and continue to engage in risky sexual behaviours. There were indications of possible race-gender differences in perceived risk of HIV infection and the practice of risky sexual behaviours. For PLWHA, there was evidence to suggest that both internalized and perceived stigma deterred women's disclosure of their HIV status to sexual partners. However, disclosure of sero-status to sexual partners did not necessarily translate into initiation of safer sex practices. Results suggest that women in this community were disadvantaged when it came to condom use negotiation. Both internalized stigma and disclosure of HIV status to a sexual partner were associated with higher levels of depression and anxiety symptoms which in turn was associated with inconsistent or no condom use. Results also suggest that there may be pathways connecting internalized stigma and condom use other than experiences of depression/anxiety and disclosure of one's HIV status to a sexual partner. We found various experiences of stigma among people living with HIV/AIDS in Khayelitsha to be associated with both increased and decreased odds of intending to have children (or more children). Experienced stigma was significantly associated with childbearing intentions. However, women's decisions to bear children appeared to be more influenced by whether they had a live-in sexual partner than experiences of stigma. We could not establish statistically significant relationships between perceived stigma and childbearing intentions both independently and after controlling for other variables. Internalized stigma was independently associated with reduced childbearing intentions but not after controlling for other relevant variables. Reported childbearing intentions among this sample of PLWHA were associated with the occurrence of at least one pregnancy after two years but are not statistically significantly related to condom use practices.